Abrupt Fen-Bog Transition Across Southern Patagonia: Timing, Causes, and Impacts on Carbon Sequestration - Loisel, Julie; Bunsen, Michael (Frontiers in Ecology and Evolution, 2020)
Fens and bogs are distinct in terms of their biogeochemistry, water table behavior, and net peat-accumulation regimes. While most peatlands start developing as fens, a large fraction of them eventually shift to bogs in a step-like ecosystem shift. This transition has traditionally been assumed to be primarily controlled by the ecosystem itself (autogenic control). Here we use 90 peat profiles from southernmost South America as a case study that illustrates a synchronous, regional-scale shift from fen to bog around 4200 years ago. In light of these results, we propose and discuss conceptual models that link environmental change (allogenic control) as a trigger to the fen-bog transition. In addition, our stratigraphic analyses show that Sphagnum deposits are associated with greater peat masses, larger soil-carbon stocks, and higher rates of peat-carbon accumulation than their non-Sphagnum counterparts, with Sphagnum bogs being characterized by soil-carbon densities over twice that of non-Sphagnum peatlands (medians = 141 vs. 56 kgC/m2). Since fens and bogs also behave differently in terms of their carbon exchanges with the atmosphere, a better appraisal of the processes involved in the fen-bog transition could help elucidate the role of this critical ecosystem shift in the past and future global carbon cycle.